The importance of optic nerve sheath hemorrhage as a postmortem finding in cases of fatal abusive head trauma: A 13-year study in a tertiary hospital - Supot Puanglumyai (2018)
© 2017 Elsevier B.V. Fatal abusive head trauma is a major cause of death in children and toddlers who suffer from cruel physical abuse. Postmortem differentiation of fatal abusive head trauma from accidental head trauma can be a complicated process. This consecutive case series study aimed to determine the role of subdural optic nerve sheath hemorrhage (ONSH) in 70 autopsy cases of children ≤3 years old in making this differentiation. The study took place over a 13 year period (between August 1st 2003 and July 31st 2016) at a tertiary hospital in Thailand. Eleven cases were diagnosed with fatal abusive head trauma and 10 were identified as being accidental closed head trauma cases. Bilateral retinal hemorrhage was noted in antemortem medical records in every hospitalized abusive head trauma case (n = 10). Upon autopsy, ONSH was observed in all 11 fatal cases of abusive head trauma (bilateral = 10 and unilateral = 1) but not in any cases of accidental head trauma (0/5). Subdural hemorrhage was found in 10 out of 11 abusive head trauma victims but not in any of the 10 with accidental head trauma. Other postmortem findings in abusive head trauma included subarachnoid hemorrhage (5/11), marked brain swelling (3/11), skull fracture (4/11) and brain contusion (1/11). This study suggests that ONSH, together with subdural hemorrhage, plays an essential role in an accurate postmortem diagnosis of fatal abusive head trauma. Therefore, an ocular investigation should be performed in all autopsy cases where child abuse is suspected and where there is no reliable history/witnesses, confession or antemortem ophthalmologic examination.